Cytogenetic analysis of children with suspected genetic disorder - Shrestha, U; Bhattacharya, S; Bhatta, NK; Jha, CB (Kathmandu University Medical Journal, 2009)
Objectives: To analyze chromosomes in children with suspected genetic disorder and to categorize the chromosomal basis of genetic disorder Materials and methods: Thirty children were selected from the patients attending genetic clinic, Department of Pediatrics, B.P. Koirala Institute of Health Sciences presenting with dysmorphic feature, mental retardation, short stature, congenital malformations and ambiguous genitalia with age between 0-15 years. Cytogenetic analysis was carried using standard peripheral blood lymphocyte culture method and G-banding technique in Cytogenetic laboratory of Department of Anatomy, B.P. Koirala Institute of Health Sciences. Results: Chromosomal disorders were identified in 33.34% (10) of children. The most common chromosomal abnormality was Down syndrome (26.67%) followed by Turner syndrome (6.67%). Conclusion: The cytogenetic analysis of children with suspected chromosomal aberration is important to uncover the contribution of chromosomal disorder in genesis of dysmorphisms, mental retardation, short stature, sexual ambiguity and congenital malformation in children and prevent further potentially unpleasant investigation being undertaken. Key words: Chromosome, suspected genetic disorder, dysmorphic feature, mental retardation, short stature, congenital malformations, ambiguous genitalia doi: 10.3126/kumj.v7i1.1763       Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 40-43